2016
DOI: 10.7863/ultra.15.10060
|View full text |Cite
|
Sign up to set email alerts
|

Is Ultrasonography More Sensitive Than Computed Tomography for Identifying Calcifications in Thyroid Nodules?

Abstract: US is more sensitive and accurate than CT for detecting calcifications in thyroid nodules. Hence, US is recommended as the preferred imaging modality for calcification detection in thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…On conventional gray-scale US, spongiform and cystic features seem to provide sufficient information to confidently rule out cancer (29) and calcification is regarded as a significant indicator of malignancy (30). In the current study, on conventional gray-scale US only 'micro-calcification' was included in the final algorithm, while shape, margin and echogenicity were excluded.…”
Section: Discussionmentioning
confidence: 85%
“…On conventional gray-scale US, spongiform and cystic features seem to provide sufficient information to confidently rule out cancer (29) and calcification is regarded as a significant indicator of malignancy (30). In the current study, on conventional gray-scale US only 'micro-calcification' was included in the final algorithm, while shape, margin and echogenicity were excluded.…”
Section: Discussionmentioning
confidence: 85%
“…Several previous studies reported that US was more sensitive than CT for the detection of calcifications in thyroid nodules. 21,27 According to Lee et al, 33 US is superior to CT in the evaluation of microcalcifications. In addition, US combined with sonography-guided FNAC is a useful method for diagnosing thyroid microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
“… 23 - 26 Therefore, calcification features in US or CT require further study. Several previous studies have shown that for detecting calcifications in thyroid nodules, US is superior to CT regardless of the calcification distribution pattern, 27 partly because the layer thickness and slice interval easily miss microcalcifications in CT. 28 We hypothesized that the presence or absence of calcification and calcification size affect the diagnostic accuracy of US and CT in predicting the benign or malignant nature of nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography is more sensitive and reliable than other imaging, in diagnosis of calcification thyroid nodules [38] . Ultrasound is routinely used to assess thyroid gland and some sonographic features may help in diagnosis of benign and malignant nodules.…”
Section: A B Cmentioning
confidence: 99%